Butterfly kisses & bittersweet tears : stories of fathers & daughters - Carlisle, Bob (Nashville : World Publishing, 1998)
Since Bob Carlisle's song "Butterfly Kisses" topped Billboard"s national charts it has become an anthem to the special love between dads and daughters. This book shares letters from fans who wanted to share their own.
Keywords: Fathers and daughters -- United States -- Anecdotes